EVALUATION THE EFFECT OF SYNTHESIZED ZINC OXIDE NANOPARTICLES FROM MYRTUS COMMUNIS L. LEAVES EXTRACT ON ESCHERICHIA COLI - A. , Safa; K, Ramina (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to estimate the effect of zinc oxide nanoparticles synthesized by Myrtus communis L. on the expression of the adhesion genes fimH and fimA in isolates of uropathogenic Escherichia coli (UPEC). The biosynthesized-ZnO NPs was characterized through several techniques including UV–vis spectral analysis, atomic force microscopy (AFM), Field Emission Scanning Electron Microscope (FE-SEM) and Fourier transform infrared (FTIR). For determination of MIC and sub-MIC of ZnO NPs, only 7 multi-drug resistant (MDR) and strong-biofilm producer E. coli isolates (harbored both fimH and fimA) were selected based on our previous work. Microtiter plate method was utilized and the results indicated that only three isolates (C1, C2 and C23) with MIC and sub-MIC (125 and 62.5 µg/ml), respectively, were selected for further experiments. Quantitative Real Time PCR was utilized for determining the gene expression of fimH and fimA in three isolates (C1, C2 and C23), with and without treatment with ZnO NPs. According to the results, the relative expressions (2-ΔΔCt) of fimA gene in C1, C2 and C23 isolates of E. coli were downregulated in 0.51-fold after treated with 125 µg/ml of ZnO NPs, while the relative expressions (2-ΔΔCt) of fimH gene in C1, C2 and C3 isolates of E. coli were upregulated in 4.42-fold after treated with 125 µg/ml of ZnO NPs.